Exploring Humor Dynamics: Cognitive Discourse Markers in Matt Rife’s Stand-Up Comedy - Putu Nadea Ayu Sarashita; Putu Nur Ayomi (RETORIKA: Jurnal Ilmu Bahasa, 2024)
Discourse markers (DMs) play a crucial role in making conversations clear and smooth, but their function in stand-up comedy remains underexplored. While previous research has examined DMs in speeches and films, little attention has been given to their use in comedy. This study focuses on cognitive DMs, which reflect thinking processes, elaboration, or self-correction, and analyzes their use in Matt Rife’s stand-up routine. Unlike other DMs, cognitive DMs convey the speaker’s mental state, guide the audience’s comprehension, and signal self-monitoring, all of which are integral to the comedic performance. The descriptive qualitative method was used to examine a popular 2023 stand-up special, focusing on how Rife uses these markers to structure his jokes and connect with the audience. This study found 151 cognitive DMs, categorized into four types: elaboration such as “like”, thinking processes like “um”, Assessment of the listener’s knowledge about utterances like “you know what I mean”, and self-correction “I mean”. The most frequently used marker was “like,” primarily serving the function of elaboration. The study shows that cognitive DMs help with timing, clarifying jokes, and engaging the audience. This research sheds light on how DMs are used in comedy and suggests that further study could improve our understanding of their role in making humor effective and engaging.